Edukasi Pentingnya 1000 Hari Pertama Kehidupan Dalam Meningkatkan Kesehatan Ibu Hamil Dan Balita Di Puskesmas Pakusari Dan Ledokombo, Jember - Rosida Hari (Warta Pengabdian, 2023)
The 1000 First Days of Life is the early period of life when you are still in the womb up to the first 2 years of life. The focus of handling nutrition in the 1000 First Day of Life is to prevent malnutrition as a major health problem in toddlers because it can hinder the process of growth and contribute to child morbidity and mortality. Based on this, community service activities were carried out with the topic "Education on the importance of the 1000 First Days of Life in improving the health status of pregnant women and toddlers in the working area of ​​the Pakusari and Ledokombo Health Centers, Jember". Counseling and socialization will be carried out from November 2022 to January 2023. The target of the service is pregnant women and mothers with toddlers. In addition, this activity also provides education to cadres so that later cadres can continue providing education activities to mothers in an effort to prevent health and nutrition problems especially in toddlers. This service activity can be carried out continuously using social media. The results of community service are in the form of articles uploaded via online news, YouTube, and journals with ISSN. Community service activities are needed which are carried out routinely through the collaboration of health education institutions and health institutions in the Jember Regency area as a follow-up to address nutritional problems in the community.